Business Intelligence Model for Sustainability of the Malaysian Rural Telecenters - Ahmad, Azizah; Abd Razak, Rafidah; Abdullah, Mohd Syazwan; Sheik Osman, Wan Rozaini; Mat Ali, Abdul Bashah; Rahmat, Abdul Razak (IBIMA Publishing, 2011)
The objective of this paper is to galvanize research on rural telecenters sustainability. The research explores the sustainability of the Malaysian rural telecenters with the support of business intelligence (BI). It is posited that BI methods and tools could play vital role in assisting telecenters implement and monitor sustainable practices. The BI information planning phase, i.e., the systematic way of defining relevant information was utilized in this research. The empirical study was conducted through interviews and observations with a range of stakeholders including ministry officers, telecenters managers and operators. A thematic model comprising of sustainability issues and challenges that arise as the roles of telecenters evolved and the relationships between these issues is developed through content analysis. This study contributes to both theory and practice by (a) the use of content analysis to discover and explicate key issues faced by rural telecenters as they aim to fill their national mission, (b) the support of the telecenters managers in enhancing participation by local communities, (c) the identification of essential capabilities for effective and socially sustainable rural telecenters,and (d) the identification of sustainability model developed which can provide a basis for future telecenter research.